Worse than ignorance the challenge of health misinformation - Schulz, Peter 1958- (Cambridge University Press, 2024)
This Element considers health misinformation and the problems it presents. The evolving communication context-changing doctor-patient relationships and developments in information technology-presents patients with a vastly enriched information landscape and new challenges to patients navigating it. These challenges are magnified as growing patient empowerment and autonomy have increased expectations for patient involvement in medical decisions. In this context, the ways people approach presented information, learn from it, understand it, and use it, exacerbate the risk that they become misinformed-believing things that are inimical to improved health. Moreover, these same processes make it difficult to correct such beliefs. Approaches building on trust between patient and professional exemplify improved communication to increase accurate patient knowledge and understanding in the service of better health. This title is also available as Open Access on Cambridge Core.